2018
DOI: 10.3897/italianbotanist.5.26855
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers for the Italian flora: 5

Abstract: In this contribution new chromosome data obtained on material collected in Italy are presented. It includes 7 chromosome counts for Centaurea (Asteraceae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Exploring the karyotype of Bulgarian flowering plants, Kuzmanov et al [25,26] reported that the C. thoermeri 2n karyotype is equal to 16. The same karyotype (2n = 16) occurs in C. nutans [27][28][29]. Our analyses of both molecular and morphological data, gave us sufficient evidence to propose restoration of C. nutans and C. thoermeri as one species with two subspecies, Table 3.…”
Section: Resultssupporting
confidence: 59%
“…Exploring the karyotype of Bulgarian flowering plants, Kuzmanov et al [25,26] reported that the C. thoermeri 2n karyotype is equal to 16. The same karyotype (2n = 16) occurs in C. nutans [27][28][29]. Our analyses of both molecular and morphological data, gave us sufficient evidence to propose restoration of C. nutans and C. thoermeri as one species with two subspecies, Table 3.…”
Section: Resultssupporting
confidence: 59%